An assessment of the biweekly collection system of RDP - Banu, Dilruba (BRAC, 2019)
The present study intended to assess the effects of the biweekly collection system of RDP on both the BRAC staff and the programme participants. Data were derived from eight VOs as well as three AOs selected randomly. Findings indicated that the biweekly collection system saves time of both BRAC staff and VO members for attending VO meetings. Members' attendance in collection meeting increased. Apparently the intensity of members' involvement in income generating activities also increased. The biweekly system reduces the operation cost of the credit programme of BRAC's RDP as it needs less staff for instalment collection. On the contrary, in the new system the size of loan instalment is big and it keeps the members always under pressure for managing money. It increases the tension of the BRAC staff to check the chance of overdue or partial repayment of loans by the VO members every month. Dependency on husband increases for using loans and repaying instalments, as members are prone to greater risk paying a double amount as instalment every two week. The biweekly system focuses more on the households' economy rather than meeting interests of the VO members towards their empowerment. Members accepted the biweekly collection system only as BRAC wanted to initiate it.